Evaluation and Mapping the Atmospheric Air Quality of Coastal Area in Bangladesh Using Remote Sensing and GIS Techniques - Hasan, Md Mahmudul; Ahmed, Asib (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
The coastal region of Bangladesh is increasingly suffering from air pollution in recent years. This study represents an analysis of the mean atmospheric column nitrogen dioxide (NO2), Sulphur di oxide (SO2), Ozone (O3), and carbon monoxide (CO) over the coastal area of Bangladesh during 2018-2022 period. Measurements of nitrogen dioxide (NO2), Sulphur di oxide (SO2), Ozone (O3) and carbon monoxide (CO) were obtained from recently launched Sentinel-5 Precursor spacecraft using Tropospheric Monitoring Instrument (Sentinel-5P TROPOMI). The aim of this study is to evaluate and visualize coastal air quality using relatively high-resolution data. PM2.5 was analyzed for the period of 1998-2019 year and the data was collected from the SEDAC website. The NO2, SO2, O3, PM2.5, and CO satellite data were then used in Google Earth Engine (GEE) and ArcGIS 10.7 software for further analysis and retrieval of the atmospheric data. The findings showed significantly high values for Khulna, Jashore, Satkhira, and Narail districts. From the NO2 observation, high values were identified in Chandpur, Shariatpur, and Lakshmipur with a highest average value of 74.2 μmol/m2. It was found that the SO2 and O3 were present significantly high over the Khulna, Bagerhat, Satkhira, and Narail districts. Particulate Matter PM2.5 exceeded BNAAQS value in every year since 1998 all over the coastal Districtswith an average value of 56 μg/m3. Years 2020 and 2021 were found much clean air than the other study years might be due to the Covid-19 Lockdown all over the country. From the trend analysis, it was found that most of the air pollutants showed an increasing trend. The interior coast was found more polluted than the exposed coast. The overall results of this study confirmed the capability of Sentinel-5P TROPOMI data to be used in monitoring the air quality over coastal areas of Bangladesh. This study highlights the widespread problem of air pollution in the coastal districts of Bangladesh and emphasizes the need for immediate action to tackle this issue. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022, P 53-65